2020
DOI: 10.3390/nano10081582
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Size-Selectivity in Laser-Based g/h Liquid Flow Synthesis of Pt and PtPd Nanoparticles for CO and NO Oxidation in Industrial Automotive Exhaust Gas Treatment Benchmarking

Abstract: PtPd catalysts are state-of-the-art for automotive diesel exhaust gas treatment. Although wet-chemical preparation of PtPd nanoparticles below 3 nm and kg-scale synthesis of supported PtPd/Al2O3 are already established, the partial segregation of the bimetallic nanoparticles remains an issue that adversely affects catalytic performance. As a promising alternative, laser-based catalyst preparation allows the continuous synthesis of surfactant-free, solid-solution alloy nanoparticles at the g/h-scale. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…[ 62 ] This supporting procedure of inorganic Au NC also leads to excellent model material for heterogeneous catalysis, which benefits from the high specific surface area of the inorganic metal NC as well as from their high surface charge. [ 63 ] Synthesis of supported catalysts from laser‐based synthesis routes was already demonstrated to be scalable to kilograms of catalysts for larger noble metal NPs [ 64 ] and transferability to Au NC with higher specific surface areas could be highly interesting. Note that surface charge tuning of ligand‐free, laser‐generated Au NCs has recently been demonstrated as an approach to understand the role of surface charge and size in heterogeneous catalysis of gold clusters supported on titania, evaluated for four different oxidation catalytic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 ] This supporting procedure of inorganic Au NC also leads to excellent model material for heterogeneous catalysis, which benefits from the high specific surface area of the inorganic metal NC as well as from their high surface charge. [ 63 ] Synthesis of supported catalysts from laser‐based synthesis routes was already demonstrated to be scalable to kilograms of catalysts for larger noble metal NPs [ 64 ] and transferability to Au NC with higher specific surface areas could be highly interesting. Note that surface charge tuning of ligand‐free, laser‐generated Au NCs has recently been demonstrated as an approach to understand the role of surface charge and size in heterogeneous catalysis of gold clusters supported on titania, evaluated for four different oxidation catalytic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…At high power MHz LSC, in-process fragmentation also contributes to a narrowed particle size distribution. Recently, it has been shown with the same polygon system that the mass fraction selectivity towards small particles is adjustable between 5 and 40% by balancing between the in-process fragmentation (downsizing) and ablation (overall productivity) particle formation pathway (Dittrich et al 2020).…”
Section: Effect Of Scan Pattern Length On the Productivity Of Lsc Witmentioning
confidence: 99%
“…The method makes alloy nanoparticles easily accessible, even in compositions difficult to produce by conventional methods, showing particular application potential and superior performance in heterogeneous catalysis (Reichenberger et al 2019). Recently, kg scale of laser-generated PtPd/Al 2 O 3 automotive exhaust gas catalysts were tested in reference reactions of CO and NO oxidation within an industrial test setting where the laser-made catalysts showed a comparable CO oxidation and even higher NO oxidation activity and durability (Dittrich et al 2020). An important contribution in the field of catalytic applications was made by Canadian researchers, who used gold-platinum alloy nanoparticles of various compositions prepared by LSC (Zhang et al 2012), (Oko et al 2014), (Oko et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Laser ablation in liquid (LAL) is a versatile method for the synthesis of nanoparticles (NPs), that enables the production of ligand-free colloids 1−4 . Compared to chemically synthesized colloids, particles generated by LAL exhibit a higher signal-to-noise ratio for laser desorption ionization mass spectrometry 5 , are suitable as reference materials for nano-toxicological assays 6 , enable the decoration of microparticles for 3D printing 7,8 , and have high potential in heterogeneous catalysis 9 even in industrial settings of automotive exhaust gas catalyst testing 10 . Furthermore, with LAL it is possible to produce molar fraction series of alloy NPs from pressed micropowder targets, even if an element miscibility gap exists 11 .…”
Section: Introductionmentioning
confidence: 99%